A framework for evaluating food security and nutrition monitoring systems - Babu, Suresh Chandra; Ergeneman, Ayca (African Journal of Food, Agriculture, Nutrition and Development, 2005)
Identifying cost and time-efficient approaches to food security and nutrition monitoring programs is fundamental to increasing the utility and sustainability. Food security and nutrition monitoring systems should be periodically evaluated to ensure that their objectives are met, and re-oriented towards the changing information needs for food policy interventions. In meeting these challenges, the role of continued evaluation of food security monitoring systems - for their impact on food security decision-making - cannot be overemphasized. The linkage between the information generated by these systems, planning and policy processes to improve food security remains weak in several sub-Saharan African countries. This paper aims at developing a framework for evaluating food security and nutrition monitoring systems. Among the criteria used for evaluation are the capacity for data processing, analysis and, reporting, timely generation of information, commitment of decision makers and cost-effectiveness. Using this framework, the paper evaluates the National Early Warning System (NEWS) and the Famine Early Warning System (FEWS) programs in Uganda, to gain useful lessons for other countries in sub-Saharan Africa. A majority of food security monitoring systems continues to be based on macro-level information and operated at the national level. Future challenges in addressing household food security will require devolution of the process of food security monitoring and intervention systems to decentralized levels. The authors also find that a sound food security and nutrition monitoring system is simple, user-driven and has the commitment of relevant decision-makers, who will use the information in planning and policy design. The paper stresses that frequent evaluation of the methods and systems of monitoring food security is essential for sustaining the commitment of decisionmakers. Also, ongoing assessments will facilitate existing monitoring systems to develop into ones that encompass the sphere of livelihood security. The use of the livelihood approach in food security monitoring in turn will support preventive and proactive solutions, rather than curative approaches to food insecurity.